A Comparative Study on Manual and Automated Software Testing Techniques at Tata Advanced Systems Limited in Nagpur - Patil, Swetali Ravindra; Rewatkar, Prof. Abhay (Journal of Neonatal Surgery, 2025)
Manual and automated software testing techniques are critical components of quality assurance in modern software development. This study examines the efficacy, efficiency, and application scope of these techniques at Tata Advanced Systems Limited in Nagpur. The research identifies the strengths and limitations inherent in both methods, emphasizing their role in optimizing development cycles, ensuring reliability, and minimizing operational risks. Through comprehensive analysis, the study reveals how manual testing excels in addressing complex, exploratory scenarios requiring human judgment, while automated testing demonstrates superiority in handling repetitive, large-scale tasks with speed and accuracy. Additionally, the comparative evaluation highlights the challenges organizations face, including resource allocation, cost implications, and skill set requirements. By leveraging a mixed-method approach, incorporating case studies, surveys, and interviews, the findings underscore the importance of strategic integration, where a hybrid model combining manual and automated techniques yields the most effective results. This research contributes to the broader discourse on software testing methodologies, offering actionable insights to industry practitioners and decision-makers aiming to enhance testing frameworks and achieve sustainable technological advancement.